2017
DOI: 10.3945/ajcn.116.145623
|View full text |Cite
|
Sign up to set email alerts
|

Modeled changes in US sodium intake from reducing sodium concentrations of commercially processed and prepared foods to meet voluntary standards established in North America: NHANES

Abstract: Background: Approximately 2 in 3 US adults have prehypertension or hypertension that increases their risk of cardiovascular disease. Reducing sodium intake can decrease blood pressure and prevent hypertension. Approximately 9 in 10 Americans consume excess sodium ($2300 mg/d). Voluntary sodium standards for commercially processed and prepared foods were established in North America, but their impact on sodium intake is unclear. Objective: We modelled the potential impact on US sodium intake of applying volunta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 24 publications
(27 reference statements)
1
11
1
Order By: Relevance
“…Modelling studies have also shown that if the NSRI targets were to be met by all food companies, that Non-Hispanic Whites would have the largest reduction in stroke incidence and mortality (24) . The most recent US-based modelling study found that if the 2014 NSRI targets were met, that the US population >1y could reduce sodium intake by 20% (28) , which is a much larger reduction predicted than our current findings which indicate that even with across-the-board reductions in the sodium content of packaged foods, sodium intake would not be reduced by more than 13%. However, our analysis simulates the reductions that could be achieved if packaged storebought foods alone had levels reduced, and do not take into account the impact that would be seen if sodium levels in foods consumed from restaurants or take-away foods were also reduced.…”
Section: Discussioncontrasting
confidence: 66%
“…Modelling studies have also shown that if the NSRI targets were to be met by all food companies, that Non-Hispanic Whites would have the largest reduction in stroke incidence and mortality (24) . The most recent US-based modelling study found that if the 2014 NSRI targets were met, that the US population >1y could reduce sodium intake by 20% (28) , which is a much larger reduction predicted than our current findings which indicate that even with across-the-board reductions in the sodium content of packaged foods, sodium intake would not be reduced by more than 13%. However, our analysis simulates the reductions that could be achieved if packaged storebought foods alone had levels reduced, and do not take into account the impact that would be seen if sodium levels in foods consumed from restaurants or take-away foods were also reduced.…”
Section: Discussioncontrasting
confidence: 66%
“…Overall, studies were heterogeneous in the way interventions and outcomes were modelled and reported, limiting between-study comparisons. As regards the type of nutrient reformulated, 20 studies focused exclusively on sodium reduction (60.6%) [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41], followed by 5 studies considering at least 2 different nutrients (15.1%) [8,[42][43][44][45], 5 studies addressing sugar (15.1%) [46][47][48][49][50] and 3 study addressing fat (9%) [11,51,52].…”
Section: Resultsmentioning
confidence: 99%
“…Target foods in the included studies were all processed foods (n = 9) [27,31,33,37,38,41,45,51,52], selected groups of nutrient-dense foods (n = 8) [11, 26, 34-36, 43, 44, 50], or single food products (n = 8) [23,24,42,[46][47][48][49]. Four studies provided estimates for more than one item [8,[28][29][30], whereas in 4 studies target foods were not specified since reformulation was modelled directly through its assumed effect on intake [22,25,32,39].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations